2013
DOI: 10.1099/mic.0.063156-0
|View full text |Cite
|
Sign up to set email alerts
|

A soluble diacylglycerol acyltransferase is involved in triacylglycerol biosynthesis in the oleaginous yeast Rhodotorula glutinis

Abstract: A soluble diacylglycerol acyltransferase is involved in triacylglycerol biosynthesis in the oleaginous yeast Rhodotorula glutinis The biosynthesis of triacylglycerol (TAG) occurs in the microsomal membranes of eukaryotes. Here, we report the identification and functional characterization of diacylglycerol acyltransferase (DGAT), a member of the 10 S cytosolic TAG biosynthetic complex (TBC) in Rhodotorula glutinis. Both a full-length and an N-terminally truncated cDNA clone of a single gene were isolated from R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…The putative DGAT3 (Glyma17g04650) gene was also highly expressed, suggesting a possible involvement of these sequences in TAG synthesis in this species, as was demonstrated for Arachis hypogaea (Saha et al , 2006), A. thaliana (Hernández et al. , 2012) and oleaginous yeast (Rani et al , 2013). A transcriptome analysis during Arabidopsis seed development showed that the expression pattern of DGAT1 was similar to DGAT3 (Peng and Weselake 2011), but the expression of DGAT3 was higher during late seed maturation.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The putative DGAT3 (Glyma17g04650) gene was also highly expressed, suggesting a possible involvement of these sequences in TAG synthesis in this species, as was demonstrated for Arachis hypogaea (Saha et al , 2006), A. thaliana (Hernández et al. , 2012) and oleaginous yeast (Rani et al , 2013). A transcriptome analysis during Arabidopsis seed development showed that the expression pattern of DGAT1 was similar to DGAT3 (Peng and Weselake 2011), but the expression of DGAT3 was higher during late seed maturation.…”
Section: Discussionmentioning
confidence: 53%
“…This pathway occurs in the cytosol and involves the acylation of monoacylglycerol to DAG and the further acylation of DAG to TAG by the action of DGAT3 . A soluble protein with DGAT activity has also been identified in oleaginous yeast (Rani et al , 2013). In addition, another soluble acyltransferase involved in TAG syntheses (LPAAT: lysophosphatidic acid acyltransferases) has been identified in Arabidopsis (Ghosh et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, another two members of DGAT3 gene family were discovered in Arabidopsis (Rani et al 2010) and castor bean. Recently, it was suggested that a soluble acyltransferase identified in the oleaginous yeast R. glutinis belongs to DGAT3 family (Rani et al 2013). The present study reports the identification and characterization of R. diobovatum DGAT2 (RdDGAT) in a TAG-deficient yeast strain.…”
Section: Introductionmentioning
confidence: 91%
“…For example, in addition to a PDAT and a type 2 DGAT, Y. lipolytica also utilizes a type 1 DGAT for TAG biosynthesis (Beopoulos et al, 2012;Zhang et al, 2012). R. glutinis possesses a soluble type 3 DGAT that is presumably part of the 10S cytosolic triacylglycerol biosynthetic complex of this species (Gangar et al, 2001;Rani et al, 2013).…”
Section: Biochemistry Of Sco Accumulationmentioning
confidence: 99%